Electronic commerce - Schnneider, Gary P; Perry, James T (Cambridge Course Technology, 2000)
Electronic Commerce provides complete coverage of the constantly changing field of electronic commerce.This book is a complete,concise introduction to electronic commerce and balanced coverage of both technology and business topics.
Keywords: Electronic commerce; Computer